THE DEVELOPMENT OF A NEW STUDENT ADMISSION PROMOTION MODEL IN THE STUDY OF NEUROSCIENCE IN THE ERA OF THE COVID-19 PANDEMIC: A Case Study at SMK Muhammadiyah 3 Yogyakarta, Indonesia - Jailani, Mohammad; Suyadi, Suyadi; Sesmiarni, Zulfani; Albar, Mawi Khusni (Idaarah: Jurnal Manajemen Pendidikan, 2021)
Abstract: The Development of New Student Admission Promotion Model in the Study of Neuroscience in the Era of the Covid-19 Pandemic The presence of the Covid-19 pandemic is very concerning for educational institutions as a whole external SMK Muhammadiyah 3 Yogyakarta. This study aims to analyze the acceptance of new students at SMK Muhammadiyah 3 Yogyakarta during the Covid-19 pandemic, based on neuroscience. The approach used in this research is the approach qualitative-descriptive by method case study. The location of this research was conducted at SMK Muhammadiyah 3 Yogyakarta. The subjects of this study were the principal, vice-principal of the curriculum section, vice-principal of the public relations section, and prospective new students. Data were obtained through in-depth interviews, observation, and documentation methods. The data analysis technique uses the Miles and Huberman model which includes data reduction, data presentation, and data verification. The results of the study show that the neuroscience-based promotion model for new student admissions is an alternative to getting new prospective students during the Covid-19 period. The neuroscience-based new student admission promotion model can respond to the frontal lobes of prospective new students well, which has implications for increasing the results of new student admissions. The promotion model for new student admissions affects the stability of the salaries of teachers and employees at SMK Muhammadiyah 3 Yogyakarta. Abstrak: Pengembangan Model Promosi Penerimaan Peserta Didik Baru dalam Kajian Neurosains pada Era Pandemi Covid-19 Hadirnya pandemi Covid-19 sangat memprihatinkan bagi lembaga pendidikan secara eksternal di SMK Muhammadiyah 3 Yogyakarta. Penelitian ini bertujuan untuk menganalisis penerimaan peserta didik baru SMK Muhammadiyah 3 Yogyakarta di masa pandemi Covid-19 berbasis neurosains. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif-deskriptif dengan metode studi kasus. Lokasi penelitian dilakukan di SMK Muhammadiyah 3 Yogyakarta. Subjek penelitian adalah kepala sekolah, wakil kepala sekolah bagian kurikulum, wakil kepala sekolah bagian hubungan masyarakat, dan calon peserta didik baru. Data diperoleh melalui metode wawancara mendalam, observasi, dan dokumentasi. Teknik analisis data menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data, dan verifikasi data. Hasil penelitian menunjukkan bahwa model promosi penerimaan peserta didik baru berbasis neurosains, sebagai alternatif untuk mendapatkan calon peserta didik baru di masa Covid-19. Model promosi penerimaan Peserta didik baru berbasis neurosains mampu merespon lobus frontal calon peserta didik baru dengan baik, yang berimplikasi terhadap peningkatan jumlah penerimaan calon peserta didik baru. Model promosi penerimaan peserta didik baru berpengaruh terhadap kestabilan gaji guru dan karyawan di SMK Muhammadiyah 3 Yogyakarta.